The Semantics of Bhinneka Tunggal Ika From The Perspective of Islam and Local Wisdom in Indonesia - Huda, M. Masrur (Proceedings of Annual Conference for Muslim Scholars, 2025)
This study analyzes the semantic meaning of the motto “Bhinneka Tunggal Ika” from the perspectives of Islam and local wisdom, which later became the basis for the motto of nationhood, statehood, and religion in Indonesia. Semantics itself uses a linguistic approach in analyzing the meaning of diversity in Indonesia. The Islamic perspective and local wisdom in diversity are interpreted as a strong foundation that underlies it and the aspects of local wisdom that are built upon it. Based on the above, the research question is: How is the semantics of “Bhinneka Tunggal Ika” understood in Islam and local cultural values in Indonesia? The purpose of this study is to explore the harmony between the principles of statehood in diversity and Islamic values and local traditions. The research method used in this study is qualitative, with semantic analysis and literature review. The results show that the spirit of “Bhinneka Tunggal Ika” is in harmony with the concept of ukhuwah in Islam and the values of mutual cooperation, tolerance, and harmony in Indonesian local culture. In conclusion, the motto of Bhinneka Tunggal Ika is not only a symbol of statehood, but also has a semantic meaning, reflecting universal values that are able to unite diversity through an Islamic approach and local wisdom